(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the role of religious policy in the formation of civic identity in the contemporary history of Uzbekistan. The study focuses on the interaction between the secular state, religious institutions, national values, and social consciousness after independence. Particular attention is given to how state policy toward religion has contributed to the strengthening of social stability, interconfessional tolerance, historical memory, and a sense of belonging to a common civic community. The article analyzes the transformation of religious policy from the early years of independence to the present stage, emphasizing the balance between freedom of conscience, preservation of secular governance, and prevention of ideological radicalization. The research also considers the pedagogical significance of this issue for history education, since the study of religious policy helps students understand the complex relationship between statehood, spirituality, national identity, and civic responsibility. The article argues that religious policy, when based on legal regulation, tolerance, and respect for cultural heritage, becomes an important factor in developing civic identity and consolidating society around shared historical and moral values.